Hubungan Tingkat Pengetahuan Dan Sikap Ibu Balita Dengan Kejadian Diare Di Puskesmas Busungbiu Ii Kabupaten Buleleng - Luh Santini; made I Made Bulda Mahayana (Poltekkes Kemenkes Denpasar, 2020)
Abstract Diarrheal disease is still a health problem in Indonesia, in general the morbidity and mortality rate in toddlers is quite high and often causes extraordinary events. This study aims to determine the relationship of knowledge and attitudes of mothers of children under five with the occurrence of diarrhea in Puskesmas Busungbiu II Buleleng Regency. This type of research is observational analytic with a cross sectional approach and statistical tests using chi-square analysis test. The number of respondents was 40 people and the determination of the sample using purposive sampling techniques. The results showed that respondents who had a good level of knowledge with toddlers who did not have diarrhea were 24 (85.7%). Whereas respondents 23 (92%) had positive attitudes with toddlers without diarrhea. Statistical test results using the chi square test on the knowledge and attitude variables towards diarrhea variables, p = 0,000 α (0.05) which means that Ho is rejected. Conclusion means that there is a significant or significant relationship between the level of knowledge and attitudes of mothers of children under five with the incidence of diarrhea. It is recommended for health workers to be more active and creative in providing health education regarding the handling of diarrheal diseases. Keywords: Knowledge, Attitude and Diarrhea